Manufacturing Integrated Design : Sheet Metal Product and Process Innovation - Groche, Peter; Bruder, Enrico; Gramlich, Sebastian (Springer International Publishing : Imprint: Springer, 2017)
The book gives a systematic and detailed description of a new integrated product and process development approach for sheet metal manufacturing. Special attention is given to manufacturing that unites multidisciplinary competences of product design, material science, and production engineering, as well as mathematical optimization and computer based information technology. The case study of integral sheet metal structures is used by the authors to introduce the results related to the recent manufacturing technologies of linear flow splitting, bend splitting, and corresponding integrated process chains for sheet metal structures. - Highlights applicability and benefits of an integrated development process through the use of case studies in the field of sheet metal structures; - Provides a perspective on an integrated development leading to products and processes; - Includes a detailed description of procedures, methodologies, and tools to integrate manufacturing, process, and materials engineering into optimized product design.